Ensayos y viveros internacionales, su utilizacion como fuente de variedades y fuente de progenitores: Ventajas y limitaciones de su uso - Rodríguez, R. (Programa Cooperativo Regional de Frijol para Centroamérica, México y el Caribe (PROFRIJOL), 1989)
International nurseries are a good source of genetic variability since they include collections of native, introduced, or improved materials. Observation and yield trials are performed to select materials; in the former, undesirable materials are discarded and the latter include an exptl. design that allows the best materials to be identified. These then, enter a 3rd phase which consists of on-farm trials. The controls used for evaluating promising materials can be local, elite, or long-term (the latter generally has broad adaptability and stable yield). (CIAT)